Bioinformatics analysis and biomolecular characterization of salivary alpha amylase as risk factor for dental caries: Analisis bioinformatika dan karakterisasi biomolekuler alfa amilase saliva sebagai faktor risiko karies gigi - Dewi, Siti Rusdiana Puspa; Irfannuddin (Makassar Dental Journal PDGI Makassar, 2024)
Salivary alpha amylase is a component in human saliva that plays important role in carbohydrate digestion. This article aims to analyze bioinformatics and biomolecular characterization of salivary alpha amylase as risk factor of dental caries. The location of this gene is 1p21.1, with nucleotide is NC_000001.11. This information was taken from National Center for Biotechnology Infor-mation's website. The number of amino acids of salivary alpha amylase is 511, with molecular weight is 577,677.82 amu. The pro-tein is stable with instability index is computed to be 23.58. Only 23 enzymes were predicted to be capable of cleaving the sa-livary alpha amylase out of a total of 37 protease. The aliphatic index is 67.12. From THMM analysis, salivary alpha amylase is found outside of membrane. It is concluded that characteristic of salivary alpha amylase can be considered as indicator for caries.